Connect with a global community of knowledgeable individuals on IDNLearn.com. Explore a wide array of topics and find reliable answers from our experienced community members.
Sagot :
Let's tackle these problems step-by-step.
### Problem 1: Find the value of [tex]\(\frac{x}{y}\)[/tex]
#### Given:
[tex]\[ \left(\frac{9}{4}\right)^{-10} \times \left(\frac{7}{18}\right)^{-10} = \left(\frac{x}{y}\right)^{-10} \][/tex]
To solve for [tex]\(\frac{x}{y}\)[/tex], let's simplify the given expression:
1. Rewrite the left-hand side:
[tex]\[ \left(\frac{9}{4}\right)^{-10} \times \left(\frac{7}{18}\right)^{-10} \][/tex]
2. Using the property of exponents [tex]\((a \times b)^c = a^c \times b^c\)[/tex]:
[tex]\[ \left[(\frac{9}{4}) \times (\frac{7}{18})\right]^{-10} \][/tex]
3. Simplify the fraction inside:
[tex]\[ \frac{9}{4} \times \frac{7}{18} = \frac{9 \times 7}{4 \times 18} = \frac{63}{72} = \frac{7}{8} \][/tex]
4. Substitute back into the equation:
[tex]\[ \left(\frac{7}{8}\right)^{-10} = \left(\frac{x}{y}\right)^{-10} \][/tex]
Since the bases are the same, we equate them:
[tex]\[ \frac{x}{y} = \frac{7}{8} \][/tex]
Thus, the correct answer is [tex]\(\boxed{2}\)[/tex].
### Problem 2: Find the value of [tex]\(x\)[/tex]
#### Given:
[tex]\[ \left(\frac{-4}{7}\right)^{-5} \times \left(\frac{-4}{7}\right)^x = \left(\frac{-4}{7}\right)^{-3} \][/tex]
To solve for [tex]\(x\)[/tex], let's use properties of exponents:
1. Combine the exponents on the left-hand side:
[tex]\[ \left(\frac{-4}{7}\right)^{-5 + x} = \left(\frac{-4}{7}\right)^{-3} \][/tex]
2. Since the bases are the same, equate the exponents:
[tex]\[ -5 + x = -3 \][/tex]
3. Solve for [tex]\(x\)[/tex]:
[tex]\[ x = -3 + 5 \][/tex]
[tex]\[ x = 2 \][/tex]
Thus, the correct answer is [tex]\(x = \boxed{2}\)[/tex].
### Problem 1: Find the value of [tex]\(\frac{x}{y}\)[/tex]
#### Given:
[tex]\[ \left(\frac{9}{4}\right)^{-10} \times \left(\frac{7}{18}\right)^{-10} = \left(\frac{x}{y}\right)^{-10} \][/tex]
To solve for [tex]\(\frac{x}{y}\)[/tex], let's simplify the given expression:
1. Rewrite the left-hand side:
[tex]\[ \left(\frac{9}{4}\right)^{-10} \times \left(\frac{7}{18}\right)^{-10} \][/tex]
2. Using the property of exponents [tex]\((a \times b)^c = a^c \times b^c\)[/tex]:
[tex]\[ \left[(\frac{9}{4}) \times (\frac{7}{18})\right]^{-10} \][/tex]
3. Simplify the fraction inside:
[tex]\[ \frac{9}{4} \times \frac{7}{18} = \frac{9 \times 7}{4 \times 18} = \frac{63}{72} = \frac{7}{8} \][/tex]
4. Substitute back into the equation:
[tex]\[ \left(\frac{7}{8}\right)^{-10} = \left(\frac{x}{y}\right)^{-10} \][/tex]
Since the bases are the same, we equate them:
[tex]\[ \frac{x}{y} = \frac{7}{8} \][/tex]
Thus, the correct answer is [tex]\(\boxed{2}\)[/tex].
### Problem 2: Find the value of [tex]\(x\)[/tex]
#### Given:
[tex]\[ \left(\frac{-4}{7}\right)^{-5} \times \left(\frac{-4}{7}\right)^x = \left(\frac{-4}{7}\right)^{-3} \][/tex]
To solve for [tex]\(x\)[/tex], let's use properties of exponents:
1. Combine the exponents on the left-hand side:
[tex]\[ \left(\frac{-4}{7}\right)^{-5 + x} = \left(\frac{-4}{7}\right)^{-3} \][/tex]
2. Since the bases are the same, equate the exponents:
[tex]\[ -5 + x = -3 \][/tex]
3. Solve for [tex]\(x\)[/tex]:
[tex]\[ x = -3 + 5 \][/tex]
[tex]\[ x = 2 \][/tex]
Thus, the correct answer is [tex]\(x = \boxed{2}\)[/tex].
We appreciate your contributions to this forum. Don't forget to check back for the latest answers. Keep asking, answering, and sharing useful information. Thank you for trusting IDNLearn.com. We’re dedicated to providing accurate answers, so visit us again for more solutions.